REPRESENTATION OF CULTURAL IDENTITY IN LIMAS HOUSE PALEMBANG - Dadang Hikmah Purnama; Mulyanto Mulyanto; Yulasteriyani Yulasteriyani (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2021)
This study analyzes the limas house as reflect of Palembang cultural identity, which is interpreted as the identity of